Effect of different crate material types for transit on production, physiological characteristics, and welfare of broilers during the summer season - Myunghwan Yu; Nuwan Chamara Chathuranga; Elijah Ogola Oketch; Jun Seon Hong; Haeeun Park; Jung Min Heo (Journal of Animal Science and Technology)
The current study investigated the impact of using iron and plastic crates during summer transportation on production, physiological characteristics, and welfare of broiler chickens. A total of 160 Ross 308 male broilers were randomly selected from a battery-caged house at 35 days of age. Their average body weight was 1,866.62 ± 36.048 g (mean ± SEM). Broilers were crated into fixed iron crates with 1.00 m (length) × 0.78 m (width) × 0.26 m (height) and plastic crates with 0.82 m (length) × 0.57 m (width) × 0.29 m (height) dimensions at 173 cm2/kg densities. Afterward, they were transported in the early morning at an average speed of 30–50 km/h for 40 minutes under 30°C and 40% relative humidity, completing a total distance of 20 km. Body weights were recorded before and after completing the journey. Following the weighing of birds, blood samples were collected for blood metabolite (cortisol, glucose, and lactate) analysis. Cervical dislocation was performed to euthanize broilers followed by breast and drumstick collection. Dressing, drumstick, and breast meat were calculated as percentages whereas respiratory frequencies were measured as the number of breaths per minute. Collected breast meat samples were utilized to analyze physiochemical parameters such as pH, color (CIE L*, a*, b*), water holding capacity, and cooking loss. Results from skin temperature assessments showed higher temperatures (p < 0.05) in broilers that were loaded into iron crates, both before (iron, 41.23 ± 0.610°C; plastic, 39.25 ± 0.065°C) and after (iron, 43.53 ± 0.723°C, and plastic, 41.63 ± 0.132°C) completing the journey. However, total skin temperature change was not significantly affected. Importantly, stress-indicating blood metabolite analysis revealed that glucose and lactate levels were lower (p < 0.05) in broilers transported in plastic crates. Nevertheless, cortisol levels remained unaffected by crate materials. Furthermore, transit losses, carcass characteristics, and physiochemical properties were also unaffected despite the dissimilar crate types. In conclusion, the study revealed that plastic is the more advantageous crating material compared to iron. Besides, plastic crates ensure meat quality and animal welfare, as evidenced by blood metabolite levels and skin temperature after transit.